PWE-308 Pelvic exenteration for primary advanced and locally recurrent rectal cancer: outcomes and experience at a single institution. (22nd June 2015) - Patsouras, D; Laliotis, A; Warner, E; Schizas, A; George, ML
Abstract : Introduction: Pelvic exenteration is a potential curative treatment for primary advanced rectal cancer (PARC) and locally recurrent rectal cancer (LRRC). The aim of such extensive radical surgery is to achieve clear resection margins. Method: A retrospective study was performed of pelvic exenteration procedures carried out between 2004 and 2014 in St Thomas' Hospital for PARC and LRRC. Factors evaluated included age, sex, neo-adjuvant therapy, type of operation, intraoperative blood loss, resection margins, 30day morbidity and mortality and overall survival. Results: Pelvic exenteration was performed in 71 patients. 51 patients were treated with neoadjuvant chemoradiation. Of the 71 patients, 52 had total, 6 had anterior and 13 had posterior pelvic exenteration; sacrectomy was performed in 4 patients. Thirty nine (39) patients (27males) with median age 61(29–80) years underwent pelvic exenteration for PARC and thirty two (32) patients (10 males) with median age 62(41–80) years had pelvic exenteration for LRRC. The median blood loss was 3700 ml (range 150015000) for PARC and 3750 ml (range 1500–15000) for LRRC. A complete resection (R0) was achieved in 67.6% of all patients; 74.4% for patients with PARC and 59.4% for patients with LRRC. Major complications (Clavien-Dindo, Grade III-IV) were 35.9% and 34.4% respectively. One patient died within 30 days. Overall survival was 32.5 months for PARC and 21.1 months for LRRC. Conclusion: Pelvic exenteration is associated with considerable morbidity but low mortality and acceptable overall survival, in the absence of other effective treatment modalities. Careful preoperative assessment and a multidisciplinary approach make this extensive surgical technique safe and feasible in an experienced centre. Disclosure of interest: None Declared.